Identity Crisis in the Social Media Era: A Dialogue between Existential Philosophy and Psychology - Muhamad Barqi Asila (CV. ITTC INDONESIA, 2026)
Social media has fundamentally changed the landscape of human interaction, bringing significant impacts to self-identity construction in the twenty-first century. This article aims to analyze the identity crisis in the social media era through a comprehensive dialogue between psychological and existential philosophical perspectives. While existing literature predominantly focuses on the empirical correlations between screen time and mental health, there remains a significant gap in understanding the ontological shifts occurring within the digital self. The method used is library research with a qualitative approach, utilizing hermeneutical phenomenology to interpret classical existential texts alongside contemporary psychological data. The results show that psychologically, social media triggers social comparison, anxiety, and self-fragmentation due to dependence on external validation mechanisms embedded in platform architectures. Philosophically, this phenomenon is read as a profound loss of authenticity, alienation, and conditions of bad faith as conceptualized by Sartre, Heidegger, and Kierkegaard. The novelty of this research lies in its synthesis of clinical psychological symptoms with ontological structures, proposing an